Quality Attributes of Breakfast Sausage As Affected by Different Types of Animal Fats - Adetunji, V.A.; Akinleye, S.B. (International Journal of Scientific Research in Biological Sciences, 2019)
Fat is one of the main components of meat sausages, along with muscle tissue and water, therefore, it has a substantial eﬀect on emulsion stability in meat products. Sausage is a ready to eat meat product usually served as breakfast. It is traditionally produced from pork and lard, but there is insufficient knowledge on the yield and nutritive qualities of breakfast sausage prepared with other animal fats. Investigations were carried out in a completely randomized design to study the effect of different fats on various physical, chemical and sensory properties of breakfast sausage. Three treatments were evaluated to test the effect of different animal fats on sausage production: sausage produced with lard (LS), sausage produced with tallow (TS) and sausage produced with sheep fat (SFS). The results obtained showed the yield from the three fat types when used for production of breakfast sausage were 83.85%, 78.52%, and 76.45% for lard, tallow and sheepfat, respectively. The mean pH value of breakfast sausage were (P<0.05) 6.46, 6.25 and 6.51 for LS, TS and SFS, respectively. Water Holding Capacity of LS (84.78%) and TS (84.82%) were similar and significantly (P<0.05) higher than SFS (82.69%). Crude protein (31.77 %) and ashes (4.83%) of sausages with lard were higher (LS)while the SFS had (25.47%) and (3.39%) for crude protein and ashes, respectively. The panelists evaluated sensory acceptance with respect to flavour, colour, texture, juiciness, tenderness and overall acceptability. LS scored the highest means for colour (5.43), flavour (5.83), juiciness (5.63), tenderness (6.13) and overall acceptability (6.83). On the other hand, SFS scored the lowest means for flavour (4.47) and juiciness (4.83). The aim of this study was to evaluate the influence of different types of animal fats on the physical, chemical composition and sensory evaluation of breakfast sausages.